The Effect of Smartphone Uses and Parenting Style on the Honest Character and Responsibility of Elementary School Students - Abdurahman, Ayi; Marzuki, Kartini; Yahya, M. Daud; Asfahani, Asfahani; Pratiwi, Endah Andriani; Adam, Ketlin Aprijane (Jurnal Prima Edukasia, 2023)
This study aims to analyze the effect of parenting and smartphone use on the honest and responsible attitude of Tipar Public Elementary School students. This study used a quantitative method with a survey method to investigate the relationship between smartphone use, parenting style, and the development of honest character and responsibility among elementary school students. Questionnaires were employed to collect data. The participants in this study were elementary school students. Tipar Elementary School will be chosen as a representative sample, and the sample size will be calculated based on statistical considerations and power analysis. The collected data were examined using relevant statistical techniques. This study reveals that parenting style positively affected students' honest and responsible attitudes by 26.3%. Smartphone use positively affects students' open and accountable attitudes by 24.0%. Parenting style has a positive effect on smartphone use, amounted 19.1%. Parenting parents and smartphones positively influence the honest and responsible mood of Tipar Public Elementary School students, 34.9%, and other factors influence the remaining 66.1%. As a result, the more positive parents' attitudes toward their children, the more honest and responsible students become. The greater students use smartphones, the better their open mindset and responsibility. Similarly, the better the parenting style and the usage of smartphones, the better students' honesty and responsibility. In contrast, the more severe the parenting style and the use of smartphones, the lower the students' open thinking and responsibility would be.